PERENCANAAN DAN PEMELIHARAAN SISTEM DRAINASE DALAM UPAYA MENGATASI GENANGAN AIR DI DESA BATU MBELIN, KABUPATEN DELI SERDANG - Indi Rezki Uli Simanjuntak; Elian Zhafira; Lestari P Winata (Nusantara Hasana Journal, 2026)
Batu Mbelin Village, located in Sibolangit District, Deli Serdang Regency, North Sumatra, has a problem of frequent water puddles in residential areas due to an inadequate drainage system. This community service activity aims to design a drainage system that suits the local hydrological conditions and provide assistance and education to the community regarding sustainable drainage maintenance. The methods used in this activity included field surveys and observations of existing conditions, drainage design based on rainfall and topographical data, and assistance to village officials and the community. The results of this activity include a drainage system design plan for Batu Mbelin Village recommended for construction to address water puddles. Additionally, the community and village officials showed enthusiasm and increased understanding of the importance of routine drainage maintenance. This activity is expected to be the first step toward achieving a sustainable drainage system and reducing the risk of water puddles in Batu Mbelin Village.